Modern approaches to the crisis management of hotel enterprises, used in world practice - B. Assaf (Вестник Российского экономического университета имени Г. В. Плеханова)
The concept of "crisis management" entered into everyday use among the managers of hotel enterprises relatively recently. As a practical discipline, crisis management began to actively develop in the 1990s. It was at this time that the objects and subjects of crisis management were determined, different approaches to definition were outlined, tasks, methods, and methods for solving them were formed. The article considers the existing approaches to the definition of crisis management, proposed by Russian and foreign scientists. The most interesting definitions of crisis management, which are used in the hotel business, are indicated. In the framework of the above definitions, examples are given on the implementation of crisis management in practice (in Russia and in foreign countries). Particular attention is paid to the classification of crises that affect the activities of hotel enterprises. Internal and external factors influencing the development of the hotel business are highlighted, and their ranking has been carried out. According to the results of the study, the shortcomings of the approaches to crisis management are presented, and a personal interpretation of the definition is proposed. World experience shows that crisis management was interested in scientists and practitioners from various fields: management, economics, finance, law, mathematical modeling, econometrics, programming, etc. Moreover, interest in crisis management arose most often at times when the world economy underwent a number of negative impacts. Currently, these phenomena have become quite frequent. Due to the fact that the markets and industries of the world have become interconnected, the financial market crisis leads to a decline in the development of the tourism industry, which in turn affects the hotel business.